A NEW METHOD FOR IDENTIFYING WYOMING BENTONITE BY ATR-FTIR - Klinkenberg M.; Dohrmann R.; Kaufhold S.; Stanjek H. (My University, 2006)
Bentonites are important for numerous industrial applications. The properties of bentonite vary depending on their genesis. Wyoming bentonites often behave in a special way with respect to industrial applications; therefore, these bentonites are of special economic interest. Bentonites of different origin differ in their mineralogical composition, chemical composition of individual minerals, surface properties, rheology, and texture. However, the analysis of these parameters is time-consuming. The aim of this study is to propose an accurate and fast analytical tool for the differentiation of bentonite products of unknown origin, particularly of Wyoming bentonites. For this purpose infrared spectroscopy with the attenuated total reflection (ATR) technique is used which allows the fast and reproducible measurement of IR bands of octahedral sheets of smectites. The extinctions and positions of these bands are quantified by fitting procedures. The attention was focused on the OH-bending region, where the position of the AlMgOH band and also the intensity ratio I(AlMgOH/(AlAlOH + AlFeOH + AlMgOH)) proved to be characteristic for Wyoming bentonites. In total 60 bentonites were analysed as standards with known origin, 13 of which are from Wyoming while the remaining 47 are from 19 other districts. To eliminate disturbing bands of typical admixtures (carbonates and illite/mica), which can influence the intensity and the position of the octahedral bands of smectites, each sample was treated with HCl and smectites were enriched by centrifugation. Applying this fast pre-treatment procedure, the AlMgOH band occurs at significantly higher wave numbers (10 cm- 1) in Wyoming bentonites than in other bentonites. In order to verify this technique, 41 products of unknown origin were analysed. Six were identified as Wyoming bentonites. Analysis of the ratio of exchangeable cations Na/(Ca + Mg + Na), which is specifically high for Wyoming bentonites, confirms the IR identification. © 2006 Elsevier B.V. All rights reserved.
Keywords: BENTONITE; IR SPECTROSCOPY; OH-BENDING REGION; SMECTITE